Hepatitis B Reactivation during Immunosuppression: From Pathogenesis to Management Strategy - Bhamidimarri, MD, MPH, Kalyan Ram; Pan, MD, Calvin (North American Journal of Medicine and Science, 2011)
Hepatitis B is one of the most common viral hepatitis that poses significant health risks in immunocompetent and more so in immunocompromised patients. Increasing scientific development and research in the fields of various autoimmune diseases and oncology have led to the evolution of several chemotherapy agents and newer modalities of treatment of these entities resulting in profound immunomodulation or immunosuppression. In the current era of under-diagnozed or under-screened population for hepatitis B, there is potential risk of developing severe or fulminant hepatitis B if such patients are exposed to immunosuppressive agents. This paper outlines the pathophysiology, clinical outcomes and explores the risk factors for hepatitis B reactivation during immunosuppression. Additionally we also propose a simplistic algorithm for the management of hepatitis B reactivation during immunosuppression that can be adopted by physicians taking care of such patients.